Penerapan Kitab Adab Al-‘Alim wa Al-Muta’allim sebagai Pembentukan Karakter Aswaja Santri di MA. Nurul Islam Sumenep - Muwafiq, Ahmad (JURNAL ILMU AL-QUR'AN DAN TAFSIR NURUL ISLAM SUMENEP, 2017)
This research aims to study the implementation of Islamic book entitled Adab al-'Alim wa al-Muta'allim that is used to shape "aswaja (following Prophet Muhammad)" characters of santri (students) at Islamic Senior High School Nurul Islam. It uses method of case study with a qualitative approach. Then, its datas are collected by observation, interview and documentation, and purposeful samplings are determined. Next, the datas are analyzed by describing the case and setting in detail in which naturalistic generalization is developed then. The results showed that the book is implemented in two approaches. Firstly, it is implemented as a policy by considering the book as reference of lesson of akhlak (morality). Secondly, it is implemented through learning process by two methods: (1) a teacher translates words in the book lexically and explain; (2) the students are required to finding the meaning of the words by themselves and explaining the findings in the next meeting. The methods of the implementation are hoped to shape characters of self responsibility, politeness and confidence that are in line with values of Aswaja.